Green Pantomime When Silence Speaks out Environmental Issues - Mohamed Mliless; Handoko (Andalas International Journal of Socio-Humanities, 2021)
Green Pantomime Theater (GPT) is a tool for promoting children environmental awareness and activism. This paper provides insight into how environmental issues can be embedded in green performances and consequently offers a model of socio- environmental change. In Morocco, GPT performances aim to change children behavior, enhance their environmental awareness, and develop their abilities to act as protectors of the environment. The status of PGT upon children has considerably changed within the Moroccan theatre context. The ‘Creativity Association for the Development of Educational Work’, under Arabic name of  جمعية لتنمية العمل التربوي إبداعات  is a Moroccan non-governmental association that employs GPT to promote environmental awareness and activism. The study examines a 45 minutes show performed by ‘the Joker’ theatre group titled البيئةهجرة ‘Environment Migration’. Within the framework of ecocriticism (Bracke & Corporaal, 2010) and visual grammar (Kress & van Leeuwen, 2006), the present work attempts to explain how silence, gestures, and visuals mirror the themes of the show. The study argues that environmental themes adopted in the performance strongly point to the Anthropocene's responsibility in destroying nature. For example, scenes on pollution, deforestation, the killing of species, and unreported and unregulated fishing (UUF) show that man has been dramatically affecting the environment. To make of the show a success, participating actors have meticulously used signs and gestures to silently express their views about a highly sophisticated issue. They have made of this show a universal performance in that anyone anywhere can perceive. Eventually, GPTs are highly recommended to identify lines of confrontation that man has with nature. Also, GPTs are important in that they represent man’s practices through gestures and signs and may provide responses for inspiring socio- ecological change.